Palladium-Catalyzed One-Pot Stereospecific Synthesis of 2-Deoxy Aryl C-Glycosides from Glycals and Anilines in the Presence of tert-Butyl Nitrite - Singh, Adesh Kumar; Venkatesh, Rapelly; Kandasamy, Jeyakumar (Synthesis, 2019)
The palladium-catalyzed one-pot synthesis of 2,3-deoxy-3-keto aryl C-glycosides is achieved from glycals and anilines in the presence of tert-butyl nitrite and aqueous HBF4 under mild conditions. This one-pot method stereospecifically provides α- and β-aryl glycosides (≥19:1 by NMR) in good yields at room temperature. The configuration at the C-3 position in the glycal determines the anomeric selectivity (i.e., α or β) of the desired products.
Keywords: palladium; C-glycosylation; aryldiazonium salts; stereospecific; tert-butyl nitrite; anilines